A man called Ove [large type] - Backman, Fredrik, 1981- (Large Print Press, a part of Cengage Learning, 2016)
Ove is an older man who has staunch principles, strict routines, and a short fuse, but behind his cranky exterior there is a story and a sadness. A chatty young couple with two daughters moves in next door and accidentally flatten Ove's mailbox. From there, a relationshp begins to form.